Pengaruh Bauran Promosi Terhadap Keputusan Konsumen Membeli Kendaraan Sepeda Motor Secara Kredit pada PT Adira Dinamika Multi Finance Cabang Pontianak - Helman Fachri; Ida Gustina (JURNAL MANAJEMEN MOTIVASI, 2014)
The research goal is to know how the effect of the promotion mix, which consists of advertising, sales promotion, public relations and publicity, and personal selling to the consumer's decision to buy a motorcycle on credit at PT Adira Multi Finance Branch Pontianak. This type of research is descriptive method with Data Collection Techniques ie primary and secondary data. The samples were taken from all the consumers who buy motorcycles on credit with as many as 100 people were selected respondents using purposive sampling technique. The analysis technique used is quantitative analysis of regression. The analysis showed that the influence of either partially or simultaneously from the variable advertising, sales promotion, public relations and publicity, and personal selling to the consumer's decision to buy motorcycles on credit at PT Adira Multi Finance Branch Pontianak. The value of the coefficient of determination (R2) of 79.20%, and the remaining 20.80% is influenced by other variables outside of this research. The value of the multiple correlation coefficient (R) obtained amounted to 0.890 indicates a very strong relationship because it is in the range from 0.800 to 1.000 correlation